1987
DOI: 10.1677/joe.0.1140033
|View full text |Cite
|
Sign up to set email alerts
|

Plasma patterns of LH, FSH and prolactin in rats with a polycystic ovarian condition induced by oestradiol valerate

Abstract: The patterns of plasma LH, FSH and prolactin concentrations were investigated in rats with a polycystic ovary condition (PCO). The condition was induced by treatment with oestradiol valerate 9 weeks before blood sampling. Serial blood samples were taken at 10-min intervals for 4 h from ten rats with PCO. All samples were assayed for LH, those from five animals for FSH and those from the remaining five animals for prolactin. In addition, five control animals with normal oestrous cycles were sampled during oestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 20 publications
(34 reference statements)
3
24
0
Order By: Relevance
“…To determine how and why this occurs, we have examined the changes in follicle populations at early intervals following hemiovariectomy in animals with PCO. In view of the significance of the plasma LH patterns in PCO (McCarthy et al, 1986Grosser et al, 1987), we would predict that any change in follicular populations should be preceded by a change in the plasma LH pattern. We have, therefore, also examined the plasma LH pattern several hours after hemiovariectomy.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…To determine how and why this occurs, we have examined the changes in follicle populations at early intervals following hemiovariectomy in animals with PCO. In view of the significance of the plasma LH patterns in PCO (McCarthy et al, 1986Grosser et al, 1987), we would predict that any change in follicular populations should be preceded by a change in the plasma LH pattern. We have, therefore, also examined the plasma LH pattern several hours after hemiovariectomy.…”
mentioning
confidence: 98%
“…Clusters of large polygonal secondary interstitial cells are abundant in the stroma (Hemmings et al, 1983;Schulster et al, 1984;Brawer et al, 1986Brawer et al, , 1989). It appears that the expression of this characteristic polycystic morphology does not reflect intrinsic ovarian pathology, but rather is the response of an essentially normal ovary to an abnormal pattern of gonado-0 1990 WILEY-LISS, INC tropin stimulation McCarthy et al, 1986;Grosser et al, 1987;Carriere et al, 1989). Examination of the histological transition from the normal to the polycystic state indicates that the polycystic morphology is really the product of complete or arrested atresia of developing secondary follicles and the absence of ovulation .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from our laboratory indicates that EV treatment produces an in tractable impairment in the hypothalamic pattern of lu teinizing hormone releasing hormone (LH-RH) delivery [3,4] which, in turn, results in selective defects in pituitary LH production, storage, and release [3]. This cascade of hypothalamic and pituitary defects ultimately translates into a unique attenuated plasma pattern of LH, to which the ovaries respond by becoming polycystic [5][6], Our investigation into the nature of the primary hypo thalamic impairment responsible for this cascade of events has revealed significant alterations in opioid func tion. We have shown that 'H-naloxone binding in the anterior hypothalamus is elevated in EV-treated rats [7].…”
mentioning
confidence: 99%
“…Young cycling adult rats exposed to E2 for 8 weeks via a subcutaneous continuous release implant [55] or a single injection of estradiol valerate (EV) [56][57][58][59] exhibited acyclicity, anovulation, and polycystic ovaries, which contained an increased number of atretic follicles and cysts with a thin granulosa cell layer and an abnormally thickened theca layer [55,57,60]. However, EV treatment decreased ovary weight and failed to provoke LH hypersecretion [56,61], hyperandrogenism, obesity, and changes in glucose and insulin concentrations, which differs significantly from human PCOS, but rats did exhibit hypertension and an increase in inguinal fat depot weight [60].…”
Section: Estrogensmentioning
confidence: 99%